Vsebnosti Cd, Pb, Hg in As v trosnjakih gliv iz gozdnate krajine Šaleške doline - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2002)
Levels of Cd, Pb, Hg and As were detremined by ICP-MS in 190 samples of higher fungi belonging to 52 species collected in the Šalek Valley in the 2000. Our findings were as follows: (1) Heavy metal levels (HML)are significantly higher in the caps of mushrooms in comparison with stems. (2) Fungi have tremendous bio-accumulative potential, therefore HML in fruiting bodies are from one order magnitude (Pb) to four orders of magnitude (As) higher in comparison with other forest fruits from the same locations. (3) Thehighest HML were determined in the followinf species: Cd - Agaricus arvensis and A. silvicola, As - A. silvicola, Coprinus atramentarius, Boletinus cavipes and Lepista nuda,Hg - A. campestris and L. nuda, Pb - Macrolepiota mastoidea, Lycoperdon perlatum and Calvatia utriformis. (4) Mushrooms should be eaten with great care due to very high contents of Hg and particulary Cd (e.g., the weekly intake rate for adult in the Šalek Valley should not exceed 50 g of Agaricus species, or 500 g of Armillaria mellea, Lepista nuda, M. procera or Boletus edulis). (5) A monitoring program of the most problematic elements in mushrooms, which is essential for performing reliable risk assessment for higher links of the food chain, must be established all over the country.
Keywords: arzen; bioindikacija; glive; kadmij; onesnaženost okolja; svinec; Šalek Valley; Šaleška dolina; živo srebro